Operational Improvements in the Shushufindi Gas Plant as an Alternative to Increasing the Availability of Liquefied Petroleum Gas (LPG) in the Ecuadorian Market - Echeverria Recalde, Maritza Ruby (2020)
Liquefied petroleum gas (LPG) is a mixture of light hydrocarbons, composed mainly of propane and butanes. It is obtained through the processing of natural gas and/or in crude oil refining processes. Currently, LPG has very varied applications, in industry, transport, agriculture, or for cooking. In Ecuador, the LPG consumption has had a growing behavior over the years and is mainly focused on the domestic, industrial, automotive, and agricultural sectors. LPG production focuses on the Esmeraldas and La Libertad refineries, and the Shushufindi Gas Plant (ShGP), which all together produce approximately 1.92 MMbl/yr. However, to satisfy the country's LPG market, the government carries out imports that represent approximately 80% of the national demand. An alternative to increase the LPG supply in Ecuador is to value the natural gas associated with the production of hydrocarbons in the Amazon region. The ShGP is located in the Sucumbios province and is a main hydrocarbon processing center for the LPG production. This work aims to carry out a technical and economic feasibility study of operational improvements that can be implemented in the ShGP to increase the supply of LPG in the national market. The study consisted of first, identifying the industrial process for the LPG production in the ShGP, where the existing unit operations, the equipment operating conditions, and the different sections of the plant were recognized based on public and available information. Second, a detailed analysis of the plant's operation was carried out using simulation tools and real data. Third, operational improvements were proposed that could be implemented in the ShGP, considering modifications in operating conditions, possible installation of expansion valves, and incorporation of a new cooling unit. Finally, a technical and economic feasibility analysis of the proposed operational improvements was carried out. The results showed that it is possible to increase the current LPG production of ShGP by 30% by incorporating a new cooling unit using ethane-based refrigerants. The estimated cost of the cooling unit is 1.5 MMUSD. However, a detailed economic study is required to define the final cost associated with the implementation and start-up of the new cooling unit.